#AfrikaansMustFall: student protest, social media and university language policy in South Africa - Vaccaro, Antonela Soledad (CIAN-Revista de Historia de las Universidades, 2024)
In this article, we take the 2015 and 2016 #AfrikaansMustFall student protest at the Universities of Stellenbosch and Pretoria and the debates around decolonization in higher education in South Africa to look at the importance of discussing language policies at that educational level. We will explore the #AfrikaansMustFall protest as an action of language management (Spolsky, 2004) from its hashtag through digital ethnography (Hine, 2004) to trace what happened with the student protests and the role of social networks for the discussion and subsequent modification of the university linguistic policy.
Keywords: student protests; language policy; social networks; universities; South Africa